The Effectiveness of Make a Match in Teaching Arabic Vocabulary to Madrasah Students - Khoiriyyah, Zahrotul; Jamroh, Nur Maya Badriyatul (Study Program of Arabic Language Teaching, 2026)
This research responds to the dominance of conventional methods that fail to spark student interest and the weak empirical evidence in similar studies. With the Make a Match model, the research aims to demonstrate enjoyable and meaningful vocabulary learning. Using a quasi-experimental Non-equivalent Control Group Design, the study involved 56 tenth-grade students from Madrasah Aliyah Al-Amiriyyah Banyuwangi, divided into an experimental and a control group. The vocabulary test instrument is valid and reliable (Cronbach's Alpha = 0.82). The analysis used the Mann-Whitney U test because the data were not normally distributed. The research results are significant. Although the initial abilities were equivalent (U = 443.50; p = 0.384), the Make a Match group improved by 43.93 points, higher than the control group, which only improved by 37.14 points. The difference in gain scores was significant (U = 522.50; p = 0.026). Observations indicate that students actively discuss, help one another, and enthusiastically participate in the game. This model transforms a passive classroom into a dynamic and collaborative one. Make a Match has proven to be an effective pedagogical strategy for improving vocabulary mastery and motivation to learn. This research provides strong causal evidence and encourages teacher innovation. Adaptive Arabic language learning for Generation Z can be realized, starting in the classroom.